Applications of date pits in foods to enhance their functionality and quality: A review - Al-Khalili, Maha; Al-Habsi, Nasser; Rahman, Mohammad Shafiur (Frontiers in Sustainable Food Systems, 2023)
Agro-byproducts are generated from bioprocessing industry that could provide functionality and bioactivity when used in foods, health supplements, and bio-composites. Date-pits are massively accumulated from date fruit processing factories, and they contain valuable bioactive compounds. Date-pits and their treated fractions can serve as a cheap additive in food products with functionality such as improved their composition in terms of fibers, proteins, fat, vitamins, minerals, polyphenols and antioxidant compounds. Additionally, it was used as natural preservative, fat replacer, tenderizing agent, hydrocolloid and emulsifying agent. Their health functionality includes antioxidant capacity, dietary fibers, caffeine free and probiotic bacteria enhancing. This paper begins with presenting the chemical composition of date-pits and their functionality in different food products. It reviews the multifunctional role of date-pits when incorporated in food products. In addition, it focuses on the applications of date-pits in many food products, such as coffee and other beverages, bakery goods, meat products, dairy products, desserts, spreads, condiments, and other food related products. Their inclusion in food products without affecting the sensory acceptability is challenging, and it varied in food products from 0.03 to 60% and 6.6 to 100% in beverages.